PENGARUH PENGGUNAAN LKS BERBASIS MODEL PROBLEM BASE LEARNING DILENGKAPI CONCEPT MAP TERHADAP KOMPETENSI IPA PESERTA DIDIK KELAS VII SMPN 3 BUKITINGGI - Yosi Elsa Wahyuny; Murtiani Murtiani; Harman Amir (Universitas Negeri Padang, 2016)
The achievement of students competence in natural science is not optimum. It is caused by the students worksheet used which cannot make students to learn independently and actively to find the concept of what they have learned. Therefore, it is necessarily the students worksheet that can be made students to learn independently and actively. Students worksheet which can be used is based on problem based learning model which is a completed concept map. The purpose of this research was to investigated affect of using student worksheet based on problem based learning model which is a completed concept map toward. It was quasy experiment and using randomized control group only design. The population of this research were all students in the first grade at SMPN 3 Bukittinggi who registered on academic year 2015/2016. The technique sampling was purpossive sampling. The Instruments used was written test for competence of knowledge, observation sheet for competence of attitude and performance assessment sheet for competence of skills. The technique of data analysis was Chi square on significance level at 0,05. Based on the result of data analysis showed that using students worksheet based on problem based learning model which is completed concept map in natural science learning, it give influence on students competence of knowledge aspect. The result of coefficient of kontingensi was 0,25. For competence of attitude aspect and skills aspect, using students worksheet based on problem based learning model which is a completed concept map in natural science didn’t give influence